5G scale networking strategy and network construction solution - Chufeng WANG; Yuan DING (Dianxin kexue)
Three telecom operators in China have issued the frequency bands of 5G trial network,the 5G operation license will be released soon,and the trial scale networking will be launched.The overall deployment strategy of 5G trial networking was expounded,and the network construction ideas and solutions of different professions were elaborated from the aspects of wireless network,bearer network and core network respectively.